The Mediating Effect of Financial Distress on the Relationship between Profitability and Value of Listed Non-Financial Firms in Nigeria - Rabiu, Naja’atu Bala; Aminu, Danladi Ahmad; Olanisebe, Moses; Salihu, Maimuna Adamu (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2023)
This study examined mediating effect of financial distress on the relationship between profitability and firm value. The prior studies have focused on the FND and firm value, individually. To date, relatively little research has been conducted in this area, the current study would like to investigate this issue and fill such a research gap in Nigerian capital market. The study used listed non-financial services firms in the Nigerian Exchange Group for the period 2011 to 2020. Purposive sampling technique was used in the study. The study used 72 firms out of the 113 non-financial services firms that were listed for the period under study. The descriptive statistics, correlation and Structural Equation Modeling (SEM) were used as techniques for data analysis while Monte Carlo model was used to determine the level of significance of the indirect effects. The study found that profitability has positive and significant effect on value, as well as financial distress of listed non-financial services firms in Nigeria. Financial distress has negative and significant effect on firm value. Finally, financial distress partially mediates the relationship between profitability and value of listed non-financial service firms in Nigeria. Hence, the study recommends among others that listed non-financial service firms in Nigeria should put profitability into consideration as it may the effect of profitability reduce financial distress and increase the value of their firms.